Relationship at work as a cause of occupational stress: the case of academic women in Vietnam. Issue 1 (December 2016) - Thanh, Le
Abstract Background The present research paper aims to bring deeper understanding and insight to perceptions and experiences of occupational stress from relationships at work in the cultural context of Vietnam. The paper also examines differences in perceptions, experiences of occupational stress from this problem and makes a comparison with perspectives in other cultures. Methods Grounded theory approach is used to study occupational stress by collecting data from in-depth interviews with 42 academic women employed at Vietnamese higher education institutions to understand the meaning, the nature and source of the occupational stress from relationships at work they experience and the impact of occupational stress on their lives. Results Cultural factors play an important role in occupational stress. Cultural factors such as power distance and hierarchy influence perception, experiences of occupational stress and the ways occupational stress is responded to. The Vietnamese context differs from other cultural contexts in the range of factors perceived as stressors for Vietnamese women. Conclusion This paper is the first grounded theory study of occupational stress among women academics in Vietnam that determines that the natural of the relationship at work play an important role in how women understand and respond to occupational stress and supports the growing evidence that occupational stress is common, global but different in other cultures.